2020
DOI: 10.1016/j.cesx.2020.100082
|View full text |Cite
|
Sign up to set email alerts
|

Single drop breakage in turbulent flow: Statistical data analysis

Abstract: To improve breakage models in the population balance framework, single octanol droplet experiments have been performed in a channel flow and recorded by high-speed camera. The study investigates impact of mother drop size on the breakage time, breakage probability, average number of daughters and the daughter size distribution for known turbulence characteristics. Each breakage event is associated with an individual turbulence level, based on the local flow characteristics. A clearly defined statistical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In fact, the time of each droplet separated from the mother droplet is different in multiple breakup events. Herø et al's work based on high‐speed photography has confirmed this process 31 . The breakup probability is defined as the ratio of the number of broken mother droplets to the total number of mother droplets.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, the time of each droplet separated from the mother droplet is different in multiple breakup events. Herø et al's work based on high‐speed photography has confirmed this process 31 . The breakup probability is defined as the ratio of the number of broken mother droplets to the total number of mother droplets.…”
Section: Introductionmentioning
confidence: 94%
“…Herø et al's work based on high-speed photography has confirmed this process. 31 The breakup probability is defined as the ratio of the number of broken mother droplets to the total number of mother droplets. Obviously, droplets are much easier to break up at a higher energy dissipation rate and a larger mother droplet size.…”
Section: A Normal Distribution Function Proposed By Valentas Andmentioning
confidence: 99%
“…In order to improve the fragmentation model in a population equilibrium framework, Herø et al. 20 examined the effect of the size of the mother droplet of monochamol on the fragmentation time, fragmentation probability, average number of sub‐droplets, and sub‐droplet size distribution, pointing out that the fragmentation model should determine the size distribution of sub‐droplets according to the size of the mother droplet, the conditions of local flow, and the nature of the system.…”
Section: Bubble Droplet Populations Of Direct Contact Evaporation Hea...mentioning
confidence: 99%
“…Over the years, masses of breakup models for liquid drops were proposed by researchers, however, the existing breakup models vary from each other in forms and predicted results, implying a lack of understanding of the drop breakup mechanism. To gain more insight into the drop breakup phenomenon, single drop breakup experiments were carried out by some research groups [1][2][3][4][5][6][7] . Results of the single drop breakup experiments verified that drop diameter, interfacial tension, and external energy input are key parameters determining the drop breakup behaviors.…”
Section: Introductionmentioning
confidence: 99%